THE RELEVANCE OF SAINT THOMAS AQUINAS' THOUGHTS IN EDUCATION IN THE ERA OF ARTIFICIAL INTELLIGENCE: BALANCE BETWEEN TECHNOLOGY AND HUMAN VALUES - Yanti Vidarosa Naibaho,; Antonius Remigius Abi; Megawati Naibaho; Hartati (Jurnal Ikhtibar Nusantara, 2026)
This study explores the ethical integration of Artificial Intelligence (AI) in education through the philosophical lens of Thomas Aquinas, addressing the tension between technological efficiency and humanistic values. While AI enhances personalized learning and accessibility (e.g., adaptive platforms like Khan Academy), it risks dehumanizing education by neglecting empathy and equity. Using qualitative philosophical analysis and systematic literature review, the research examines Aquinas’ principles of natural law, virtue ethics, and telos (purpose) to propose a framework balancing AI innovation with moral education. Findings reveal that Aquinas’ emphasis on reason, character formation, and social justice aligns with modern needs to mitigate AI’s pitfalls, such as data privacy concerns and reduced human interaction. The study concludes that AI should complement, not replace, human educators, with policies prioritizing ethical training, inclusive access, and curricula integrating Aquinas’ virtues (e.g., justice, empathy). This synthesis offers a holistic approach to ensure AI serves as a tool for human flourishing in education.